2 - The origins of the feminist movement in Senegal: A social history of the pioneering Yewwu-Yewwi - Oumar Kane; Hawa Kane (African Sociological Review, 2018)
In this paper, we explain the emergence of Yewwu-Yewwi, the first feminist movement in Senegal. The genealogy, as well as the objectives of the movement, are reconstructed and we analyze the sociopolitical context of its birth as well as the difficulties that the movement faced in order to impose its legitimacy on the Senegalese political, associative and institutional scene. The role of its central figures is drawn in all its complexity and Yewwu-Yewwi’s action and relative success is precisely delineated through archival material and interviews with the protagonists of the process. Finally, the determinants of the elitist tendency of the movement are described in connection with the sociological, historical and political context of the time.